Factors That Make Up Students' Free Time in Developing Immunity Against Harmful Habits (Eurasian Research Bulletin, 2022)
The factors of everyday activity of students are described in this article, correct organization of the daily routine and of leisure of pupils, prophylaxis of pernicious habits at pupils, practising music, painting, literature, theatre and other types of art, rich in content organization of leisure of pupils.